Quest for Collective Intelligence in the Internet Public Sphere. Comparative Case Study and Cognitive Processes Analysis - Rafal OLSZOWSKI; Urszula ZIEMIANCZYK (Communications of International Proceedings, 2021)
The subject of the presented comparative case study is the phenomenon of collective intelligence (CI) in the online public sphere. Intelligence that appears in online communities is understood as a form of a distributed ability, which arises from the collaboration and competition between many individuals in the Internet. The purpose of the presented study was an analysis of group cognitive processes specific for the manifestations of CI, appearing in the 8 selected online projects implemented in the Central-Eastern European countries. Additionally, 2 projects from Western Europe, considered in the scientific literature as valuable examples, were selected for comparison purposes. In these projects, we evaluated the 4 main cognitive processes specific for collective “thinking”: perception (collective sensing), problem-solving, decision making, and collective memorization (including learning and gaining feedback). The results revealed, that most cognitive processes in the analyzed projects are working satisfactorily, with the exception of collective memory, which works only to a very limited extent. A presented guideline for future policymakers is to develop a shared memory system, to which all community members should have access.
Keywords: Collective Intelligence; Online Projects; Cognitive Processes; Public Sphere; E-Participation